Biomechanical analysis of the turn in front crawl swimming - Pereira, S.; Araujo, L.; Freitas, E.; Gatti, R.; Silveira, G.; Roesler, H. (Biomechanics and Medicine in Swimming X, 2006)
The main purpose of this study was to investigate the contribution of the dynamic and kinematic variables to the performance in freestyle. The turns of 38 swimmers were analyzing using an underwater force platform and two video cameras that sup-plied. Angle of knee flexion (AK), maximum normalized force peak (FPn) and contact time (CT) were measured as variables. Through investigation of the contribution of the variables AK, PMn and CT to the variable TT it was possible identify that PMn explains the greatest percentage of variance in turn performance (17,70%). The relation between AK and PMn indicated that larger values of AK (smaller flexions) tend to provide larger values of PMn (r = 0,38). Start from the results analysis, it can be suggested that angles of knee flexion between 110 and 120 degrees tend to provide larger force peaks, smaller contact times and smaller turn times, reaching the best performance of the crawl stroke turn execution.